Development and the art of nutritional maintenance. Issue 5 (14th September 2022) - Gardner, David S.; Gray, Clint
Abstract: Development from early conceptus to a complex, multi-cellular organism is a highly ordered process that is dependent on an adequate supply of nutrients. During this process, the pattern of organ growth is robust, driven by a genetic blueprint and matched to anticipated body mass with high precision and with built-in physiological reserve capacity. This apparent canalisation of the developmental process is particularly sensitive to variation in environmental stimuli, such as inappropriate drug or hormone exposure, or pattern of nutrient delivery. Significant variation in any of these factors can profoundly affect fetal and neonatal growth patterns, with later detriment for physiological function and/or reserve capacity of the resultant adult, with potential health impact. This paradigm shift in science has become known as the Developmental Origins of Health and Disease (DOHaD). Over the last 30 years, many animal and clinical studies have vastly expanded our fundamental knowledge of developmental biology, particularly in the context of later effects on health. In this horizons article, we discuss DOHaD through the lens of nutritional quality (e.g. micronutrient, amino acid, NSP intake). The concept of ' Quality' was considered undefinable by Robert Persig in his book, ' Zen and the Art of Motorcycle Maintenance '. Here, development and the art of nutritional maintenance will define quality in terms of the pattern of nutrient intake, the quality of development and how each interact to influence later health outcomes.